Development of A Guided Inquiry-Based Practicum Guide E-Book In Biology Learning - Dimas Ontowiryo, Moch. Alawi; Wijayanti, Erna; Norra, Bunga Ihda (Biosfer: Jurnal Tadris Biologi, 2024)
Biology learning can take the form of practical activities that require practical instructions as activity guides. Practical instructions formed in the E-book model will provide advantages in terms of practicality and efficiency. The aim of this research is to make students more active in the biology learning process. This type of research is Research and Development (R&D). The development design used is ADDIE. This research data collection used interview and questionnaire methods. The results of the development of the guided inquiry-based interactive practical e-book were validated by media experts 93% (very feasible), material experts 96% (very feasible), and learning methodology experts 95% (very feasible). From the three validators, an average score of 94% can be taken, so that the guided inquiry-based interactive practicum guide E-book can be declared "Very Eligible" for testing. The results of the readability test for biology teachers received a score of 100% with the criteria "Very Eligible". Meanwhile, for students in class XI MIPA, 20 students were used, namely 10 students in class XI MIPA 5 and 10 students in class.ABSTRAK: Pembelajaran biologi dapat berupa kegiatan praktikum yang membutuhkan petunjuk praktikum sebagai panduan kegiatan. Petunjuk praktikum yang dibentuk dalam model E-book akan memberikan kelebihan dalam hal kepraktisan dan efisien. Tujuan penelitian ini adalah membuat siswa lebih aktif dalam proses pembelajaran biologi. Jenis penelitian ini adalah Research and Development (R&D) desain pengembangan yang digunakan adalah ADDIE. Pengumpulan data penelitian ini menggunakan metode wawancara dan angket. Hasil pengembangan E-book petunjuk praktikum interaktif berbasis inkuiri terbimbing di validasi oleh ahli media 93% (sangat layak), ahli materi 96% (sangat layak), dan ahli metodologi pembelajaran 95% (sangat layak).  Dari ketiga validator dapat diambil nilai rata-rata sebesar 94%, sehingga E-book petunjuk praktikum interaktif berbasisi inkuiri terbimbing dapat dikriteriakan “Sangat Layak” untuk diujikan. Hasil uji keterbacaan pada guru biologi mendapatkan skor 100% dengan kriteria “Sangat Layak”. Sedangkan pada siswa kelas XI MIPA menggunakan 20 siswa yaitu 10 siswa kelas XI MIPA 5 dan 10 siswa kelas XI MIPA 6 mendapatkan hasil nilai rata-rata 80% dengan kriteria “Layak” untuk digunakan.